When is neuropsychological testing medically necessary for children on medicaid in New Mexico?. Issue 1 (2nd January 2019) - Kaufman, Noah K.; Mullins, Carola; Davis, Andrew S.; Tonarelli, Silvina; Sandoval, Hugo; Ramos-Duran, Luis
ABSTRACT: Healthcare for poor children, also known as Medicaid, is disproportionately relied upon by citizens of poor states such as New Mexico, where (a) there are more unintended pregnancies, (b) domestic violence during and after pregnancies occurs with regularity, (c) youth substance use is much more common, (d) crime rates are some of the worst in the country, (e) many never graduate from high school, and (f) incarceration is often inevitable. Yet, there is a dearth of research into the neuropsychological health of these children. Meanwhile, nonneuropsychologists working for managed care organizations routinely deny authorization for neuropsychological testing based on a lack of medical necessity. The present article addresses the question of neuropsychological medical necessity using community-based neuropsychological data from New Mexico collected on Medicaid and non-Medicaid youth via retroactive chart review. Downstream fiscal implications that are related to the eventual cost of mental illness and crime among those with poor neuropsychological health are discussed.